Study on Chocolate Production from Coconut Oil and Palm Oil Shortening - Limphapayom, Wilaisri (International Coconut Community Journal, 2013)
Chocolate is a well-known dessert all over the world. The original chocolate is made from cocoa products: cocoa bean and cocoa butter. Research and Development on low-fat chocolate process were conducted for value addition of coconut oil and Thai fruit. This chocolate processing study composed of (1) coconut oil fractionation, (2) chocolate formulation and (3) shelf-life storage determination. Accordingly, fatty acids composition of the blend of coconut fat and palm oil shortening were determined. It was found that the said product composed of Caproic acid 0.47±0.12%, Caprylic acid 5.65±0.31%, Capric acid 5.14±0.14%, Lauric acid 42.56±0.28%, Myristic acid 16.31±0.18%, Stearic acid 14.55±0.13%, Oleic acid 9.26±0.17%, and Linoleic acid 2.16±0.35%. The saturated fatty acids and unsaturated fatty acids found in this product were 88.57±0.14% and with 11.42±0.81%, respectively. The range of melting point is 260C-330C and oxidative stability is 14.2 to 16.7 hours. The chocolate formula of pale and dark chocolate 1kg composed of coconut fat, palm oil shortening, and lecithin as emulsifier in same amounts such as 250g, 100g, and 0.5g. However, icing sugar and defatted cocoa powder are in different amounts; the icing sugar in pale chocolate and dark chocolate is 350g and 450g while the defatted cocoa powder in pale chocolate and dark chocolate is 200g and 300 g, respectively. These chocolate products have physical properties similar to the chocolate products produced from cocoa butter. The shelf life of these products is 3 months.